2013
DOI: 10.1371/journal.pone.0057183
|View full text |Cite
|
Sign up to set email alerts
|

Non-Alcoholic Fatty Liver Disease Is Associated with an Increased Incidence of Atrial Fibrillation in Patients with Type 2 Diabetes

Abstract: BackgroundThe relationship between non-alcoholic fatty liver disease (NAFLD) and atrial fibrillation (AF) in type 2 diabetes is currently unknown. We examined the relationship between NAFLD and risk of incident AF in people with type 2 diabetes.Methods and ResultsWe prospectively followed for 10 years a random sample of 400 patients with type 2 diabetes, who were free from AF at baseline. A standard 12-lead electrocardiogram was undertaken annually and a diagnosis of incident AF was confirmed in affected parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
155
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(166 citation statements)
references
References 36 publications
5
155
1
5
Order By: Relevance
“…Again, no patients were treated with pioglitazone or glucagon-like peptide-1 receptor agonists, which have been shown to reduce hepatic steatosis [1,9,25] and improve cardiac function [26,27]. Finally, our novel finding of a significant association between NAFLD and larger left atrial volume might also be of pathophysiological relevance in the explanation of recent observations documenting that type 2 diabetic patients with NAFLD are at risk of atrial fibrillation [28,29]. Collectively, our results suggest that NAFLD may contribute to impairments of both active and passive LV diastolic properties that are most probably additive to the myocardial defects already present in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 75%
“…Again, no patients were treated with pioglitazone or glucagon-like peptide-1 receptor agonists, which have been shown to reduce hepatic steatosis [1,9,25] and improve cardiac function [26,27]. Finally, our novel finding of a significant association between NAFLD and larger left atrial volume might also be of pathophysiological relevance in the explanation of recent observations documenting that type 2 diabetic patients with NAFLD are at risk of atrial fibrillation [28,29]. Collectively, our results suggest that NAFLD may contribute to impairments of both active and passive LV diastolic properties that are most probably additive to the myocardial defects already present in type 2 diabetes.…”
Section: Discussionmentioning
confidence: 75%
“…A cohort of 19 NAFLD adults compared to age, gender and BMImatched controls were shown to have a thicker left ventricular wall in both systole and diastole as well as decreased longitudinal shortening than those without fatty liver [50] . One of the consequences of diastolic dysfunction is atrial fibrillation and NAFLD has been shown to have an increased risk (OR = 4.49) of atrial fibrillation which was independent of age, gender, hypertension, and left ventricular hypertrophy and pr interval [51] . Thus adults with NAFLD have changes in cardiac structure and function that may predate overt cardiac artery disease.…”
Section: Ref Methods Resultsmentioning
confidence: 97%
“…However, Targher et al showed that NAFLD was associated with an increased incidence of CVD in T2DM patients, independent of traditional CVD risk factors and MetS components [6]. They also found an increased incidence of atrial fibrillation in NA-FLD-T2DM patients independently of important clinical risk factors for atrial fibrillation [31].…”
Section: Discussionmentioning
confidence: 98%